2014
DOI: 10.1158/0008-5472.can-14-0218
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EphA3 Inhibits Cancer Growth by Disrupting the Tumor Stromal Microenvironment

Abstract: Eph receptor tyrosine kinases are critical for cell-cell communication during normal and oncogenic tissue patterning and tumor growth. Somatic mutation profiles of several cancer genomes suggest EphA3 as a tumor suppressor, but its oncogenic expression pattern and role in tumorigenesis remain largely undefined. Here, we report unexpected EphA3 overexpression within the microenvironment of a range of human cancers and mouse tumor xenografts where its activation inhibits tumor growth. EphA3 is found on mouse bon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 45 publications
(63 reference statements)
3
75
0
1
Order By: Relevance
“… 109 Bispecific human IgG1     Ifabotuzumab/KB004/IIIA4EPHA3afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumor growth inhibition over control antibody in DU145 or 22Rv1 xenograft miceVail et al. 132 Humanized IgG1     Bemarituzumab /FPA144FGFR2bafucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumour growth inhibition in FGFR2-overexpressing gastric cancer xenograft mouse model over isotype control(b)Humanized IgG1     Afucosylated TrastuzumabHER2afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumor growth inhibition over fucosylated trastuzumab in KPL-4 xenografts in human FcγRIIIα miceJunttila et al. 133 Humanized IgG1     TrasGEX/ GT-MAB7.3-GEX/Glycooptimized Trastuzumab-GEXHER2ReducedHuman glycoengineered production cell lines (GlycoExpress technology)Potent Her2 + BT474 tumor growth inhibition in nude mice but exhibited similar tumor volume and number of regression between fucosylated and reduced fucosylated antibodies(c)Humanized IgG1     Lumretuzumab /RG7116/RO5479599/ GE-HuMAb-HER3HER3ReducedCoexpression with GnT-III and α-ManII in CHO cells (GlycoMAb Technology)Enhanced survival of SCID-beige mice with A549-B34 NSCLC xenograftsMirschberger et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
“… 109 Bispecific human IgG1     Ifabotuzumab/KB004/IIIA4EPHA3afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumor growth inhibition over control antibody in DU145 or 22Rv1 xenograft miceVail et al. 132 Humanized IgG1     Bemarituzumab /FPA144FGFR2bafucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumour growth inhibition in FGFR2-overexpressing gastric cancer xenograft mouse model over isotype control(b)Humanized IgG1     Afucosylated TrastuzumabHER2afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumor growth inhibition over fucosylated trastuzumab in KPL-4 xenografts in human FcγRIIIα miceJunttila et al. 133 Humanized IgG1     TrasGEX/ GT-MAB7.3-GEX/Glycooptimized Trastuzumab-GEXHER2ReducedHuman glycoengineered production cell lines (GlycoExpress technology)Potent Her2 + BT474 tumor growth inhibition in nude mice but exhibited similar tumor volume and number of regression between fucosylated and reduced fucosylated antibodies(c)Humanized IgG1     Lumretuzumab /RG7116/RO5479599/ GE-HuMAb-HER3HER3ReducedCoexpression with GnT-III and α-ManII in CHO cells (GlycoMAb Technology)Enhanced survival of SCID-beige mice with A549-B34 NSCLC xenograftsMirschberger et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
“…28 The effects of disrupting the tumor microenvironment by targeting Eph receptor tyrosine kinases are currently being studied in both solid and hematologic malignancies. 100,101 EphA3 is important in cell positioning during fetal development and is not expressed in normal adult tissues. However, EphA3 expression has been demonstrated in various hematologic and solid tumors.…”
Section: Disrupting the Myelofibrosis Bone Marrow Microenvironmentmentioning
confidence: 99%
“…88,89 In solid malignancies, EphA3 is preferentially expressed in tumor stroma, vasculature, and bone marrow-derived mesenchymal stem cells. 101 Data from Vail et al suggest that Eph is not ligated in stromal cells derived from the solid tumor so it is kinase-dormant. In solid tumors, kinase-dormant Eph lead to cell-cell adhesion, invasion and tumor maintenance.…”
Section: Disrupting the Myelofibrosis Bone Marrow Microenvironmentmentioning
confidence: 99%
“…Previously, we have found that during ephrin-induced adhesion of leukaemia cells overexpressing EphA3, an important cancer target (Day et al, 2013;Vail et al, 2014), PTP-PEST (also known as PTPN12), together with other focal adhesion proteins such as FAK and paxillin, is recruited into EphA3 signalling complexes (Wimmer-Kleikamp et al, 2008). PTP-PEST is a ubiquitously expressed cytosolic protein tyrosine phosphatase that plays important roles in similar developmental processes to Ephs, including neurogenesis, vasculogenesis and mesenchymal development (Sirois et al, 2006).…”
Section: Introductionmentioning
confidence: 99%